How do work placement learning instructional methods enhance students' learning experiences?. Issue 6 (December 2022) - Ogba, Francisca Ngozi; Okolie, Ugochukwu Chinonso; Udu, David Agwu; Idike, Ifeanyi Matthew
This study focuses on identifying the most effective instructional methods of work placement learning (WPL) delivery that industry-based instructors can adopt to enhance students' learning experiences. Employing interview and focus group methods, the authors learned from 39 participants, including 21 higher education students who had undertaken WPL in various industries and 18 industry-based instructors who have been providing placement learning tasks (instructions) to students. Focusing on the four most effective methods identified from the thematic analysis – namely, exploration, elaboration, engagement and evaluation (operationalised as the 4E instructional methods) – the authors analyse how the 4E instructional methods contribute to facilitating students' learning experience during work placements. Drawing on experiential learning theory and the findings of the study, recommendations are offered for the adoption of the 4E instructional methods for the effective delivery of WPL tasks to facilitate students' work-related knowledge, skills and attitudes for their future career development and employability.